Analysis of the Implementation of Health Promotion Programs on Diarrhea Disease Control at Kuala Public Health Center, Bireuen Regency - Teuku Syahlidin (Pena Cendekia Insani, 2021)
Diarrhoea can deplete the body's electrolyte and water reserves, most notably sodium and potassium. Kuala public health centres, Bireuen Regency, reported an annual increase in the number of children with diarrhoea, from 445 in 2014 to 505 in 2015. The purpose of this study was to determine the extent to which a health promotion program for diarrhoea management was implemented in 2016 in Kuala public health centres, Bireuen Regency. The study adopted a qualitative methodology. It took place between February and June 2016 in Kuala public health centres, Bireuen Regency. The informants who provided information during the study were the subjects of the research. Primary data were gathered through in-depth interviews with informants and field observation, whereas secondary data were gathered through documentary analysis and observation at the public health centres. According to the research, the Kuala public health centres health promotion program was implemented by incorporating it into each public health centre's working units. Diarrhoea was addressed in the Kuala public health centres work area through a health promotion approach. At Kuala public health centres, the health promotion infrastructure, particularly in the media, was inadequate and limited in its capacity to handle diarrhoea. Individuals lacked comprehension as a result of ineffective counselling. Kuala public health centres are recommended to develop a health promotion program through cross-sector collaboration and the use of health promotion media in order to raise public awareness and understanding of diarrhoea..